Hemodynamic Monitorization of the Burn Patient - Ahmet Coşar; Burak Eşkin (Galenos Yayinevi, 2011)
Hemodynamic monitorization is the basic component of the medical care of the burn patients. It provides valuable information of the cardiopulmonary performance which is essential in the rapid diagnosis and treatment in the case of hemodynamic disturbance. The clinical importance of any monitorization parameter, associated risks - benefits, cost effectivity, and also assessment and management skills of the health care providers should be taken into consideration in the selection process of the monitorization method. This paper reviews the methods of the hemodynamic monitorization for the clinical care of the burn patients. (Journal of the Turkish Society Intensive Care 2011; 9 Suppl: 11-20)